Estudio de la factibilidad para la creación de una fábrica productora de pantalones jeans en la ciudad de nueva Loja provincia de Sucumbíos - Rosero Ramón, Amanda Elizabeth (2018)
In the city of Nueva Loja you want to know if it is feasible or not to create a jeans factory since there are no equal factories in this city, this research must be done to see if it is feasible and at the same time it will generate new sources of work for this city. This study is being carried out in order to satisfy the unsatisfied demand for pants that exists in the city of Nueva Loja, seeking to design pants that are fashionable and trend with an added value that the pants designed can be tailored for young people between 15 at 24 years of age. For the present project, a market study was conducted through surveys since there are no historical data, it was possible to determine the tastes and preferences that are pants with characteristics similar to the most recognized brands Fiara for women and Diesel for men, and so on. to be able to satisfy the unsatisfied demand of our product. The company will be located in the Julio Marín neighborhood of the City of Nueva Loja in a strategic and easily accessible sector. As results of the research we obtained The profitability of this company is 66.87% of the total investment so it is recommended that this project be executed, since it is feasible and that in 2.6 years we will be able to recover the investment and as a cost benefit we have that for every dollar invested we will recover 0.26 cents